Metaphor in product design: قيس والي عباس (Al-Academy, 2016)
Addresses current research to the subject of metaphor as a field important in the design of industrial product, so it was a problem search: Does industrial product which is designed mainly to reflect the principle of metaphor role in receiving, and how the application of mechanisms theory correct as stipulated in institutions metaphor properly for this orientation in achieving those metaphors. What are the relations of reciprocity that influenced the establishment of the design and construction of the system for industrial product, the objectives of the research were standing on the interactive nature of the relations between the metaphor and the process of industrial product design? And identify strengths and weaknesses in the processes employing the principle of metaphor in the design process of the industrial product, by detecting the nature of metaphors and projections in this direction. After providing mechanisms detailed on the subject through the theoretical framework, eating researcher range of industrial products (cars) and discussed mechanisms employ the principles of metaphor in its various forms, the researcher to a range of results, including consistency requirements of functionality in industrial products, explicitly and compressor with features borrowed Nickname of it, which produced designs and hired elements in a harmonious and consistent with the formal construction of an alias of it.. As researcher conclusions alia, that the mystery and complexity of the receipt of the function a malfunction causing the deficiency in the aesthetic aspect of the product manufacturing based on the metaphor is, so it is essential that characterized the product is easy to use and simplicity with hiring good for advanced technology, on the other hand an interactive process between the product and the user another tributary imparted aesthetic values in the product derived from the functional efficiency of him